Chronic Kidney Disease as A Potential Risk Factor for Uveitis: A 13-Year Nationwide Population-Based Cohort Study in Taiwan. (17th November 2022) - Lin, Chun-Ju; Tien, Peng-Tai; Lai, Chun-Ting; Hsia, Ning-Yi; Chang, Cheng-Hsien; Bair, Henry; Chen, Huan-Sheng; Yang, Yu-Cih; Lin, Jan-Ming; Chen, Wen-Lu; Tsai, Yi-Yu
ABSTRACT: Purpose: To investigate whether patients with chronic kidney disease (CKD) are at increased risk of uveitis. Methods: Data was collected from the Taiwan National Health Insurance system and included patients newly diagnosed with CKD between 2000 and 2012. The endpoint of interest was a diagnosis of uveitis. Results: 30, 256 CKD patients and 121, 024 matched comparisons were analyzed. CKD patients were found to have a significantly higher cumulative uveitis incidence. Through multivariate Cox regression analysis, the CKD group was found to have higher risk of developing uveitis (adjusted hazard ratio 1.51). After stratified by gender, age, and comorbidities (hypertension, diabetes, and hyperlipidemia), the increased risk of uveitis in CKD patients remained significant. Conclusions: Patients with CKD were found to have higher risk of developing uveitis. For patients over 18 years old and with hypertension, diabetes, or hyperlipidemia, the presence of CKD was demonstrated as an additional crucial factor for uveitis development.